PENDAMPINGAN HALAL DAN FOOD SAFETY PENGELOLAAN MAKANAN DI PESANTREN AL-HUSNA JONGGOL KABUPATEN BOGOR - Sri Rahayu; Emma Rachmawati; Mulyanti; Rina Yuliana Subur (Panrita Abdi - Jurnal Pengabdian pada Masyarakat, 2023)
Food is an essential thing for human life; as a supporter of growth and development for living things, it acts as a supplier of energy in activities and a supplier of materials to build and replace tissues in carrying out work and maintain the body's defense against disease. The problem faced by the Al-Husna Jonggol Islamic Boarding School in Bogor Regency is the provision of the needs of the students while studying at the Islamic boarding school, including halal food and good for the body so that there are no more cases of food poisoning because the management has not met safety standards so that education and assistance in food management are needed from the start. From contamination prevention, Personal Hygiene, temperature and time of food handling, and food management flow. The results of the evaluation of community service activities were in the santri and female students group, the average value of pre-test = 50 and post-test = 84.40 of several 50 people, and there was a significant difference in p-value = 0.001. In the management group, the average pre-test = 52.67 and post-test = 83.33 from 15 people, and there was a significant difference in p-value = 0.001. The evaluation of the achievement of food management quality standards that do not meet the criteria is the storage of raw materials, the accuracy of the temperature management, the use of Personal Protective Equipment, and infrastructure. Suggestions for managers should apply food safety in food management so that food poisoning does not occur.  ---  Makanan merupakan suatu hal yang sangat penting bagi kehidupan manusia sebagai penunjang pertumbuhan dan perkembangan bagi makhluk hidup. Permasalahan yang dihadapi Pesantren Al-Husna Jonggol Kabupaten Bogor dalam pengelolaan makanan belum memenuhi standar safety sehingga diperlukan pemberian edukasi dan pendampingan pengelolaan makanan mulai dari pencegahan kontaminasi, personal hygiene, temperatur dan waktu penanganan makanan serta alur pengelolaan makanan. Tujuan kegiatan ini memberikan rekomendasi kepada pemerintah untuk mengeluarkan kebijakan kepada para penanggung jawab pesantren agar memperhatikan pengelolaan makanan. Hasil kegiatan kelompok santri dan santriwati didapatkan nilai rata-rata pretest = 50 dan posttest = 84.40 dari 50 orang  signifikan ada perbedaan dengan p-value = 0,001 < α. Pada kelompok Pengelola didapatkan nilai rata-rata pretest = 52.67 dan post test = 83.33 dari 15 orang signifikan ada perbedaan p-value = 0,001 < α. Secara keseluruhan pengelolaan makanan melalui pencapaian indikator mutu halal dan food safety mencapai standar 64% yang belum sesuai standar adalah penyimpanan bahan baku, ketepatan suhu pengelolaan, penggunaan Alat Pelindung Diri (APD) dan sarana prasarana. Saran bagi para pengelola hendaknya menerapkan food safety dalam pengelolaan makanan agar tidak terjadi keracunan pada makanan yang dihasilkan.